Ejercicio de circuito y su incidencia en el desarrollo de la resistencia aeróbica en los estudiantes de bachillerato de la Unidad Educativa José María Estrada Coello, del cantón Babahoyo, Provincia Los Ríos - Aviléz Cerezo, Franklin Patricio (2019)
The system of exercises per circuit is well known in the sports environment and especially when the objective is to improve the resistance in its different forms and phases, for which a set of exercises designed to work on certain muscles and organs is selected, this group of previously selected and oriented exercises are synchronized in time and space so that the organism acquires a certain form and resistance during the development of the same which makes it look for results that benefit or optimize its functioning. The work of the resistance is aimed at certain stages of training, which is why in the present research it is aimed at high school students and its objective is to analyze how the exercise of the circuit influences the development of aerobic resistance in students. of the José Maria Estrada Coello Educational Unit, for which non-experimental qualitative research was used when interpreting students' behavior in the face of the application of circuit and quantitative exercises when working with mathematical results and statistical applications. the results, the modality is of field when collecting the surveys and interviews and bibliography when collecting the information coming from texts, scientific articles or magazines, applied to a population of the baccalaureate of random form. In the results obtained it was observed that there are few times that circuit exercise is applied in classes, so the balance between the contribution and the oxygen expenditure is not achieved and there is no circuit exercise program destined to achieve the balance between the contribution and expenditure of oxygen and the consumption of glycogen, glucose and fats, for which the application of a circuit exercise program to develop aerobic resistance in high school students is proposed.